Chemistry of ozone in water and wastewater treatment : from basic principles to applications - von Sonntag, Clemens, 1936-2013; von Gunten, Urs, 1959- (London : IWA Pub., 2012)
Chemistry of Ozone in Water and Wastewater Treatment book will discuss mechanistic details of ozone reactions as much as they are known to date and apply them to the large body of studies on micropollutant degradation such as pharmaceuticals and endocrine disruptors that is already available.
Includes bibliographical references and index.
Keywords: Water -- Purification -- Ozonization; Sewage -- Purification -- Ozonization; Ozone -- Reactivity